2006
DOI: 10.1007/s00214-005-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Actinide Chemistry in Solution, Quantum Chemical Methods and Models

Abstract: 16 pagesTheoretical modeling of actinide complexes requires access to structural parameters, information on electronic, vibration and rotation energy levels and thermodynamics properties. This article presents a critical review of theoretical studies of actinide chemistry in gas-phase and in solution and a comparison with experimental data in order to assess the applicability and accuracy by which various electronic structure theories can predict the required quantities. The quality of the basis set, the impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
130
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(141 citation statements)
references
References 81 publications
9
130
2
Order By: Relevance
“…However, we do not agree with Rotzinger that 87.6 % weight on the HF reference rules out the use of MP2, when there are no apparent near degeneracy effects. On the contrary, both our results presented here and in reference [2] (p. 156), and the results presented in Table 1 in the article by Rotzinger, clearly show that MP2 can be used on uranyl-(VI) complexes. The ground state of metal ions with open dshells can in principle be described by one determinant, but for this to be true, in particular in strong ligand fields, the electron configuration must be chosen with care.…”
supporting
confidence: 45%
See 3 more Smart Citations
“…However, we do not agree with Rotzinger that 87.6 % weight on the HF reference rules out the use of MP2, when there are no apparent near degeneracy effects. On the contrary, both our results presented here and in reference [2] (p. 156), and the results presented in Table 1 in the article by Rotzinger, clearly show that MP2 can be used on uranyl-(VI) complexes. The ground state of metal ions with open dshells can in principle be described by one determinant, but for this to be true, in particular in strong ligand fields, the electron configuration must be chosen with care.…”
supporting
confidence: 45%
“…[ 2] In a recent paper [3] Rotzinger has found it expedient to base his previous claim on computational evidence and we applaud this. Despite considerable computational efforts his conclusions are still flawed; his own calculations (and some additional ones made by us) demonstrate very clearly that it is entirely proper to use the MP2 method in computational studies of the uranyl(VI) ion.…”
Section: *A C H T U N G T R E N N U N G (M=o) and P*a C H T U N G T Rmentioning
confidence: 91%
See 2 more Smart Citations
“…The self-consistent inclusion of spin-orbit coupling in structure determination is a challenging task, and at present this is only tractable for relatively small systems. Calculations for small actinide molecules have found that spin-orbit effects modify bond lengths by <0.1Å and vibrational frequencies by a few percent; [29][30][31] similarly, spin-orbit effects have little influence on lattice structures for the actinide dioxides. 32 Given the more compact nature of the lanthanide 4f wavefunctions as compared to the actinide 5f electrons, spin-orbit coupling is expected to play an even lesser role in bonding and thus the influence on geometry should be minimal.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 99%